Isolation and Capability of Dark Septate Endophyte Against Mancozeb Fungicide - Jean Nihana Manalu; Bonny Poernomo Wahyu Soekarno; Efi Toding Tondok; Surono Surono (Institut Pertanian Bogor, 2020)
Mancozeb is a group member of dithiocarbamat fungicides that most widely applied in the field. The use of mancozeb causes residues that have negative effects on agricultural production system and on agricultural environment. This research aimed to obtain dark septate endophyte (DSE) fungal isolates that are tolerant to mancozeb fungicide. The study was consisted of three steps, i.e., the isolation of DSE fungi from chili roots, the effect of DSE fungal isolates on chili seeds, and the growth ability of DSE isolates on medium supplemented with mancozeb. Thirteen DSE fungal isolates were isolated from chilli pepper roots and grown in the field assumed to be contaminated by pesticides. The isolates of DSE fungi caused the growth of chili seeds were normal and abnormal. Seven DSE isolates were able to grow well at PDA medium suplemented with mancozeb at concentrations of 100, 200, 400, and 800 ppm with different levels of relative growth inhibition. Mancozeb on PDA medium influenced the mycelial growth and colony color of DSE fungal isolates. The biomass of DSE fungal isolates were reduced when they were grown at malt extract broth (MEB) medium suplemented various levels of mancozeb. Keywords: dithiocarbamat, relative growth inhibition, tolerant